2020
DOI: 10.1007/s11238-020-09744-6
|View full text |Cite
|
Sign up to set email alerts
|

Need, frames, and time constraints in risky decision-making

Abstract: In two experiments, participants had to choose between a sure and a risky option. The sure option was presented either in a gain or a loss frame. Need was defined as a minimum score the participants had to reach. Moreover, choices were made under two different time constraints and with three different levels of induced need to be reached within a fixed number of trials. The two experiments differed with respect to the specific amounts to win and the need levels. The 2 Â 2 Â 3 design was a within-subject design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(59 citation statements)
references
References 29 publications
(41 reference statements)
8
46
5
Order By: Relevance
“…Only the results of Experiment 1 support the hypotheses: We observed slightly stronger framing effects among the 0-Need condition. This result supports the findings of Diederich et al [30] and Mishra and Fiddick [32]. Furthermore, stronger framing effects were found among participants who were assigned to the no-ID condition of Identity.…”
Section: Plos Onesupporting
confidence: 90%
See 3 more Smart Citations
“…Only the results of Experiment 1 support the hypotheses: We observed slightly stronger framing effects among the 0-Need condition. This result supports the findings of Diederich et al [30] and Mishra and Fiddick [32]. Furthermore, stronger framing effects were found among participants who were assigned to the no-ID condition of Identity.…”
Section: Plos Onesupporting
confidence: 90%
“…To compare our results with other studies that focused on need [29,30] we included Frame (gain, loss) and Time (1s, 3s) as additional factors. Probability to win a lottery was included to complete the design.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…A third approach consists in limiting participants’ ability to engage in effortful cognitive processing of the framed statement using either time pressure or cognitive load (e.g., Whitney et al, 2006). Various studies found that time pressure amplifies framing effects, as it affects the depth of the statement processing and favors a fast and intuitive decision process (Diederich & Wyszynski, 2017; Diederich et al, 2018; Guo et al, 2017; McElroy & Conrad, 2009). Some framing effect studies used dual-task paradigms to investigate the impact of cognitive load on the processing of framed statement (i.e., McElroy and Conrad, 2009; Whitney et al, 2008).…”
Section: Methodsmentioning
confidence: 99%